The autophagy-related protein beclin 1 shows reduced expression in early Alzheimer disease and regulates amyloid β accumulation in mice - Pickford, Fiona (American Society for Clinical Investigation, 2008)
Autophagy is the principal cellular pathway for degradation of long-lived proteins and organelles and regulates cell fate in response to stress. Recently, autophagy has been implicated in neurodegeneration, but whether it is detrimental or protective remains unclear. Here we report that beclin 1, a protein with a key role in autophagy, was decreased in affected brain regions of patients with Alzheimer disease (AD) early in the disease process. Heterozygous deletion of beclin 1 (Becn1) in mice decreased neuronal autophagy and resulted in neurodegeneration and disruption of lysosomes. In transgenic mice that express human amyloid precursor protein (APP), a model for AD, genetic reduction of Becn1 expression increased intraneuronal amyloid β (Aβ) accumulation, extracellular Aβ deposition, and neurodegeneration and caused microglial changes and profound neuronal ultrastructural abnormalities. Administration of a lentiviral vector expressing beclin 1 reduced both intracellular and extracellular amyloid pathology in APP transgenic mice. We conclude that beclin 1 deficiency disrupts neuronal autophagy, modulates APP metabolism, and promotes neurodegeneration in mice and that increasing beclin 1 levels may have therapeutic potential in AD.